(3eLeY GdHdGZIs
(3ChdgG (B:s
(3abQC EfJNHJgG heG EfJgjJ Edjg ef CYdGe MHQ EbJVHJgG hLeYJgG heG hLOJg ai cdGe GdHdZGA ef daX jYO ai GdSMQ GdMdGd s
(3BNQgG (B:s
(3hai cdGe GdMSf Cf KhekG QcHhG GdCaQGS GdYJGb hdHShG GdKjGH GdQbGb hChSYhG OhQge hVjbhG bHhQge hSefhG CHOGfge hgRdhG COjGfge jbhd CHZjG di gGVhekG hjdc hgd JgVe EdG Ojfc s
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
Keywords: (3GdeLGejYs